Product-service system aimedat eradication of hunger and encouraging sustainable agriculture (Revista Brasileira de Contabilidade e Gestão, 2021)
The eradication of hunger and poverty and the encouragement of sustainable agriculture are the agenda for discussions at a global level and are a long way to go. As guidelines, there are the seventeen Sustainable Development Goals (SDGs) of the United Nations, which group goals to be achieved aiming at a healthier and more sustainable world. The Product-Service System (PSS) aims at dematerialization, focusing on results and problem solving. Therefore, the objective of the study is to highlight important guidelines for the creation of proposals that address the PSS and serve as an incentive for its application. The research gap was defined based on bibliometric analysis, which highlights the relevance of the PSS, ODS, urban agriculture, zero hunger in isolation in the academic environment, but when the subjects are grouped, little is found.
Keywords: Product-Service System; Zero Hunger; SDGs; Sustainable Agriculture